Kolesterol dan Tekanan Darah Lansia di Posyandu Abiyoso Polkesbaya - Christyaningsih, Juliana; Rusyadi, Luthfi; Minarti, Minarti; Mamik, Mamik; Pestariati, Pestariati; Mutiarawati, Diah Titik; Suliati, Suliati; Sasongkowati, Retno; Woelansari, Evy Diah; Suhariyadi, Suhariyadi; Istanto, Wisnu; Endarini, Lully Hanni; Museyaroh, Museyaroh (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2023)
As people age, the physical state of the human body will gradually deteriorate due to a decrease in the quantity of cells present, leading to a gradual reduction in functionality referred to as the aging process. In elderly humans (aged more than 60 years) excessive cholesterol levels and high blood pressure are one of the causes of diseases such as heart disease which has been recognized by WHO as the number one cause of death in the world. The buildup of fatty deposits on the linings of blood vessels has the potential to lead to obstructions within the blood vessels. The objective of this initiative is to enhance understanding regarding the hazards associated with cholesterol. This outreach effort took place in July 2023, conducted at Posyandu Abiyoso, Surabaya Health Polytechnic. The activity consists of several processes 1). conducting a survey of the location of the Abiyoso posyandu of the Surabaya Health Polytechnic, 2). Opening registration and taking participants' personal data, 3) conducting participant health interviews, 4). Checking cholesterol levels and blood pressure of participants. From the community service activities carried out, it was found that 42 of the 65 (64.6%) participants who took part in the examination at the integrated service post had high cholesterol levels, and 60 of the 65 (92.3%) participants had high blood pressure or hypertension. By conducting health checks on cholesterol levels and blood pressure, there is an expectation that the society will come to realize and comprehend. the dangers of hypertension and hypercholesterolemia so that the community can prevent the occurrence of sustainable diseases.